2021
DOI: 10.1186/s12884-021-03770-0
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal care coverage and its determinants in Sri Lanka: analysis of the 2016 demographic and health survey

Abstract: Background Postnatal care (PNC) is important for preventing morbidity and mortality in mothers and newborns. Even though its importance is highlighted, PNC received less attention than antenatal care. This study determines the level of PNC coverage and its determinants in Srilanka. Methods This is a secondary analysis of the 2016 Demographic and Health Survey. Receiving full postnatal care (FPNC) was defined with a set of indicators to detect adequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The reconstruction of wealth index was done after consulting with DHS experts. Previous studies using DHS data sets have also adapted this methodology [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reconstruction of wealth index was done after consulting with DHS experts. Previous studies using DHS data sets have also adapted this methodology [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with Sri Lanka, Ethiopia's demographic and health survey (EDHS 2016), and Mertule Mariam. 23,26,41 In our study, participants who had no transport for a PNC visit were 48% less likely to utilize PNC service compared to those who had transport. Despite the fact that transport availability is a significant factor for postnatal care utilization, no study identified it previously.…”
Section: Discussionmentioning
confidence: 61%
“…However, in an Asian country, Pakistan, 93.0% of the mothers who delivered preterm babies were diagnosed with anemia (10). Further, underweight might be co-existed with anemia (7), and it is evidenced in this study that 37.5% of the anemic mothers were underweight…”
Section: Pregnancy Complicationsmentioning
confidence: 60%
“…More than half of the mothers (54.9%) did not report pregnancy complications. It might be due to paying home visits and health education regarding pre-conception preparation and the prevention of pregnancy complications by Public Health Midwives (7). Among the pregnancy complications, pre rupture of membrane (46.3%) and hypertension (24.2%) were in high incidence and they matched with a Sri Lankan study (27,28).…”
Section: Pregnancy Complicationsmentioning
confidence: 82%
See 1 more Smart Citation